THE ROLE OF ENGLISH PROFICIENCY IN IMPROVING ACCOUNTING WORKPLACE PERFORMANCE - Elsa Panggabean; Jesisca Butar butar; Ardiko sinuraya (Journal of Language Education (JoLE), 2026)
This study aims to analyze the importance of English proficiency in the accounting workplace in the current global and digital business environment. Accounting professionals are expected not only to master technical accounting knowledge but also to possess adequate English skills to support communication and workplace performance. This study employs a qualitative descriptive method using a literature review approach by examining various relevant sources related to English proficiency, accounting practices, workplace communication, and professional competence. The findings identify five major areas requiring English proficiency in accounting workplaces: financial document interpretation, report writing, workplace communication, accounting software operation, and career competitiveness. The study also shows that limited English proficiency may hinder accounting staff in understanding work instructions, interpreting financial information, preparing reports, and adapting to global workplace demands. Furthermore, English proficiency contributes to improving professional communication, work effectiveness, and career opportunities in the accounting field. This study contributes to the understanding of English proficiency as an essential supporting competence for accounting professionals and highlights the importance of integrating English skills development into accounting education and professional preparation programs.